Estudio de la actividad periodística e interactividad que promueven los diarios La Hora Loja y Centinela en sus versiones digitales y redes sociales. Periodo marzo-julio-2015. Propuesta alternativa - Torres Calva, Alicia Soledad (2016)
This research is born with a need to know about the process of digital information in virtual versions of the daily La Hora-Sentinel Loja and Loja and interactivity with the public. The study has ideas about the characteristics of digital media, as well as the beginning, elements and trends, also the analysis of web portals, content sections, published information and social networking sites, as well as input from specialists in online journalism Dr. Ramón Salaverría and Mg. Sandra Crucianelli also highlight the views of Lic. Boris Sarango and Ing. Bolívar Lojan as knowledgeable on the subject and who are dedicated to developing and publishing digital information entering daily to these websites and how could it miss version-makers and post the information on these websites and the version of citizenship lojana as to the digital versions of newspapers studied.